Produksi Biomassa, Analisis Nutrisi dan Senyawa Bioaktif Jamur Grigit (Schizophyllum commune) - Rida Oktorida Khastini; Rani Rahmawati (Biotropic : The Journal of Tropical Biology, 2023)
Schizophyllum commune, a wild edible mushroom, has gained significant attention due to its potential as a valuable source of biomass, nutrients, and bioactive compounds. This study aims to explore the production of mycelial biomass and analyze its nutrient and bioactive compound content to be applied as a raw material in food production. The Schizophyllum commune was cultivated in potato dextrose broth media with temperature (25, 30, 35, and 40oC) and pH treatments (3, 7, and 8) to determine the optimal conditions for biomass production. Mycelia biomass was harvested and extracted. Nutrient and bioactive compounds were analyzed. Results showed that 30oC and pH 7 give the highest biomass production. Proximate analysis revealed that the mushroom's mycelia biomass contained high protein, low fat, and fiber. The analysis also demonstrated a rich profile of bioactive compounds, including flavonoid and phenolic compounds, respectively1 2,32 ± 0,95 dan 415,72 ± 15,23 g/100 g mycelia dry weight. Schizophyllum commune exhibits promising prospects for mycelial biomass production.